Pengaruh Penggunaan Game Edukasi Wordwall terhadap Minat Belajar Bahasa Arab Siswa Madrasah Tsanawiyah - Zahabiyah, Mufidah Hasnah; Mardani, Dadan; Arifin, Moh Mas’ud (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the effect of using Wordwall, an educational game-based learning medium, on the Arabic learning interest of eighth-grade students at Madrasah Tsanawiyah Ma’had Al-Zaytun. The problem underlying this research is the students’ low interest in learning Arabic, which is influenced by the perception that the subject is difficult and monotonous. The method used in this study is quantitative with a pre-experimental design of the one-group pretest–posttest type. The research population includes all eighth-grade students, totaling 405, with a sample of 44 students selected using cluster sampling techniques. The research instrument was a learning interest questionnaire consisting of 30 statement items using a five-point Likert scale. Data analysis included validity, reliability, normality, and linearity tests, as well as paired t-tests and simple linear regression. The results showed an increase in the average learning interest score from 102.16 (pretest) to 110.91 (posttest). The significance value of p < 0.001 indicates a significant effect of using Wordwall on increasing students’ Arabic learning interest. The determination coefficient (R²) of 0.539 indicates that 53.9% of the variation in students’ learning interest can be explained by the use of the Wordwall medium. These findings confirm that the use of Wordwall creates an interactive and enjoyable learning atmosphere, capable of enhancing students’ motivation and active participation in Arabic learning. Therefore, digital game-based media such as Wordwall are recommended as innovative alternatives to improve students’ learning interest in madrasah settings. Keywords: Arabic Language, Learning Interest, Educational Game, Wordwall, Interactive Learning.